Role Head School in Motivating Teachers Improving Teaching Creativity in History Learning in Senior High School 7 Palu - Nurfirayani H; Mahfud M Gamar; Idrus Rore; Suyuti (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The discussion in this paper is (1) What is the role of the principal in motivating teachers at SMA Negeri 7 Palu? (2) How is the creativity of teachers in teaching history at SMA Negeri 7 Palu? The purpose of this paper is: (1) To describe the role of the principal in motivating history teachers at SMA Negeri 7 Palu. (2) To describe the creativity of teachers in teaching history at SMA Negeri 7 Palu. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. This research was conducted at SMA Negeri 7 Palu City, located at Tawaeli Jl. Baiyah Raya No. 29 Palu City, Central Sulawesi Province. After the data was successfully collected and analyzed qualitatively with a flow model including data reduction, data presentation and drawing conclusions. The results of the study indicate that the principal plays a role as a facilitator, motivator, and supervisor in motivating teachers. This role is realized through the provision of facilities and training, providing motivation and rewards, and implementing learning supervision. The teaching creativity of history teachers is seen from the ability to arouse student motivation and activeness, actively involve students, and use a variety of learning methods and media. Thus, the role of the principal contributes positively to increasing the teaching creativity of history teachers at SMA Negeri 7 Palu.